Exponential Stability of Impulsive Stochastic Functional Differential Systems - Zheng Wu; Hao Huang; Lianglong Wang (Abstract and Applied Analysis)
This paper is concerned with stabilization of impulsive stochastic delay differential systems. Based on the Razumikhin techniques and Lyapunov functions, several criteria on pth moment and almost sure exponential stability are established. Our results show that stochastic functional differential systems may be exponentially stabilized by impulses.